ANALISIS RASIO RISK-BASED CAPITAL SEBAGAI PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN ASURANSI JIWA DI INDONESIA - Ellen Putri Manggarini (Prodi Magister Manajemen Universitas Wijaya Putra, 2023)
The present research purposively seeks the predictive effect of RBC ratios to forecast the emerging of financial distress on life insurance company in Indonesia. The predictor variables-used are 1) total assets, 2) total liabilities, 3) credit risks, 4) liquidity risks, 5) market risks, 6) insurance risks, and 7) operational risks. The data-collections are derived from the financial statements of 10 life insurance company samples, which had higher financial performance than the other companies, along the periods of 2017-2021. The results-generated, from multiple linear regression analysis, are showing some significant values of predictive effect on all of seven predictors to forecast financial distress, either partially or simultaneously. These findings may be positioned as reference by life insurance companies in Indonesia to manage their financial risks so that company may be able to mitigate the emerging financial distress in the future.